The conditional effects of self-control in situational action theory. A preliminary test in a randomized scenario study. Issue 11 (2nd November 2018) - Pauwels, Lieven J.R.
ABSTRACT: This study focuses on the perception-choice process in the Situational Action Theory of Crime Causation (SAT). The effect of self-control ability is studied in conditions of conflict or correspondence between personal morality and circumstantial characteristics. We demonstrate a conditional effect of self-control ability on choosing a violent response in two scenarios. While we demonstrate that self-control ability matters in cases of moral conflict, we demonstrate some findings that seem to be at odds with theoretical tenets of SAT. The impossibility to empirically distinguish processes of perception and choice, together with SAT's current measure of self-control ability may partially be responsible for this empirical ambiguity.